Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Dalam Penyajian Laporan Keuangan KSP Kopdit Bahtera Ende - Yulita Londa (Jurnal Riset Akuntansi, 2024)
The aim of the study was to determine the Application of Financial Accounting Standards for Entities Without Public Accountability in presenting the Financial Statements of KSP Kopdit Bahtera Ende. This type of research is descriptive research. The research location was carried out at KSP Kopdit Bahtera Ende, Jl. Prof.W.Z.John, Paupire Village, Ende, East Nusa Tenggara. Data collection techniques in this study are by using: Observation, Interview, Documentation, and Literature Study The application of SAK ETAP in the financial reports of KSP Kopdit Bahtera has generally implemented SAK ETAP and is in accordance with the rules and provisions of SAK ETAP, only one component of the financial report is missing, namely the Notes to the Financial Report. This is proven by the financial report as of 31 December 2023 presented by KSP Kopdit Bahtera.